Paragliding Events & Festivals: Catalyzing Aero-Sports Tourism Development in India - Kumar, Ajay; Kumar, Aman (Integrated Journal for Research in Arts and Humanities, 2024)
India’s diverse geographical landscape and rich cultural history make it an ideal destination for paragliding events and festivals, highlighting its potential for aero sports tourism in the world. India has been the host of the Paragliding World Cup, and Paragliding Accuracy Pre-World Cup integrating with various cultural events and festivals. Paragliding destinations of Himachal Pradesh, Uttarakhand, Maharashtra, and Kerala have gained popularity among the paragliding community worldwide by hosting paragliding “events & festivals”. This study has evaluated the potential of the paragliding destination of various states in India and the role of paragliding “events and festivals” in aero-sports tourism development in India. After analyzing the data from the secondary sources found the various challenges for aero sports tourism in India. Managerial implication has underlined the importance of strategic planning required by state tourism departments, paragliding associations, and local communities to incorporate music and dance festivals with paragliding events. Skill development and training programs for local youth, development of the infrastructure, sustainable environmental practices, and effective marketing and promotion will all contribute to the growth of paragliding tourism in India. Findings highlight the incorporation of local culture (dance music & food) into paragliding festivals, which promotes India’s rich heritage. Organizing events and festivals at Aero sports destinations attract tourists as well as benefits the local economy, resulting in job growth. Sustainable environment-friendly practices and community participation can reduce environmental damage and it will promote a sense of ownership among locals. The results underline the importance of empowering local communities to benefit from paragliding tourism development. Paragliding festivals not only paragliding pilots and tourists, but they also serve as an effective destination marketing tool, promoting lesser-known destinations and contributing to India's long-term Aero-sports tourism development goals.